2014
DOI: 10.1002/zaac.201400056
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic and SERS Activities of Tryptophan‐EDTA Capped Silver Nanoparticles

Abstract: This report describes the synthesis of silver nanoparticles (AgNPs) by in situ reduction of silver nitrate with designed ethylenediaminetetraacetic acid‐tryptophan bioconjugates. Conjugation of EDTA was chosen to augment water solubility of resulting conjugate, which in turn facilitates synthesis of AgNPs in aqueous medium. Various spectroscopic and microscopy techniques were employed to characterize the EDTA‐tryptophan capped AgNPs. The nanoparticles show excellent catalytic activity towards reduction of p‐ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Another plausible explanation for the decreased accuracy in SERS is the use of EDTA during plasma collection. EDTA is a molecule for complexing metal ions and it has been found that its carboxylate groups can bind to nanoparticles surface and be responsible for the generation of new spectral bands [37]. This could potentially obscure the detection of the biological information in the derived spectra.…”
Section: Discussionmentioning
confidence: 99%
“…Another plausible explanation for the decreased accuracy in SERS is the use of EDTA during plasma collection. EDTA is a molecule for complexing metal ions and it has been found that its carboxylate groups can bind to nanoparticles surface and be responsible for the generation of new spectral bands [37]. This could potentially obscure the detection of the biological information in the derived spectra.…”
Section: Discussionmentioning
confidence: 99%
“…33 EDTA-capped AgNPs yielded absorptions at 1061 cm À1 , 1401 cm À1 , 1632 cm À1 and 3446 cm À1 , which were assigned to C-O single-bond vibrations, asymmetric carboxylate group stretching, amide-I C]O stretching, and O-H stretching vibrations, respectively. 34 This IR spectrum strongly conrmed the capping of the AgNPs through direct bonding of EDTA.…”
Section: Ftir Studiesmentioning
confidence: 98%
“…EDTA was chosen as a capping agent because of its good anionic interaction with metal sulfides and control of morphology. [23][24][25] The effect of precursor material concentration (i.e. Ni-(NO 3 ) 2 •6H 2 O, CH 4 N 2 S, and EDTA) on the formation mechanism of nickel sulfide hierarchical structures and phase control was investigated.…”
Section: Introductionmentioning
confidence: 99%